Comparison of Oryza sativa and Oryza brachyantha Genomes Reveals Selection-Driven Gene Escape from the Centromeric Regions. Issue 8 (2nd July 2018) - Liao, Yi; Zhang, Xuemei; Li, Bo; Liu, Tieyan; Chen, Jinfeng; Bai, Zetao; Wang, Meijiao; Shi, Jinfeng; Walling, Jason G.; Wing, Rod A.; Jiang, Jiming; Chen, Mingsheng
Abstract : High-confidence assemblies enabled comparative genomics analyses of the centromeric regions of Oryza genomes and provided insight into centromere evolution. Abstract: Centromeres are dynamic chromosomal regions, and the genetic and epigenetic environment of the centromere is often regarded as oppressive to protein-coding genes. Here, we used comparative genomic and phylogenomic approaches to study the evolution of centromeres and centromere-linked genes in the genus Oryza . We report a 12.4-Mb high-quality BAC-based pericentromeric assembly for Oryza brachyantha, which diverged from cultivated rice ( Oryza sativa ) ∼15 million years ago. The synteny analyses reveal seven medium (>50 kb) pericentric inversions in O. sativa and 10 in O. brachyantha . Of these inversions, three resulted in centromere movement ( Chr1, Chr7, and Chr9 ). Additionally, we identified a potential centromere-repositioning event, in which the ancestral centromere on chromosome 12 in O. brachyantha jumped ∼400 kb away, possibly mediated by a duplicated transposition event (>28 kb). More strikingly, we observed an excess of syntenic gene loss at and near the centromeric regions (P < 2.2 × 10 −16 ). Most (33/47) of the missing genes moved to other genomic regions; therefore such excess could be explained by the selective loss of the copy in or near centromeric regions after gene duplication. The pattern of gene loss immediately adjacent to centromeric regions suggests centromere chromatin dynamics (e.g., spreading or microrepositioning) may drive such gene loss.